2021
DOI: 10.1021/acs.macromol.1c00165
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Block-Polyelectrolytes on an Oppositely Charged Surface

Abstract: Electrostatic interaction is widely considered to be the main driving force of the adsorption of polyelectrolytes (PEs) on an oppositely charged surface. Therefore, the alteration of charge distribution as a result of varying PE chain structures will directly affect the performance of the adsorption behaviors in the system at a certain monomer concentration. In this work, we studied the effects of chain structure (chain length, N m) as well as sequence variables including charge fraction and blockiness on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…Polyelectrolyte induced charge reversal of surfaces has been already published in the literature and it was related to entropy effects, ion correlations and hydrophobic interactions. [51][52][53] The trend in the stability ratios is in good agreement with the zeta potential values if one considers the presence of repulsive forces of electrostatic origin. Accordingly, at low doses, where the particles possess considerable positive charge, aggregation did not occur, i.e., the dispersions were stable.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Polyelectrolyte induced charge reversal of surfaces has been already published in the literature and it was related to entropy effects, ion correlations and hydrophobic interactions. [51][52][53] The trend in the stability ratios is in good agreement with the zeta potential values if one considers the presence of repulsive forces of electrostatic origin. Accordingly, at low doses, where the particles possess considerable positive charge, aggregation did not occur, i.e., the dispersions were stable.…”
Section: Resultssupporting
confidence: 71%
“…Polyelectrolyte induced charge reversal of surfaces has been already published in the literature and it was related to entropy effects, ion correlations and hydrophobic interactions. 51–53…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Atif integrates both cDFT and a self-consistent field theory (SCFT). [32,33] The users can choose one of the two methods arbitrarily to start their projects. In order to make it unnecessary for users to either know the computer language (such as C++ or FOR-TRAN) or seek an experienced collaborator, this designed software can be controlled completely via a readable input file.…”
Section: Introductionmentioning
confidence: 99%
“…Selective adsorption, however, introduces an interesting variation on the adsorption problem that the sequence of stickers in the polymer chain leads to important modifications in adsorption phenomenology compared to the case of nonselective adsorption. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The selectivity can be provided by monomers characterized by different charges as in polyampholyte or other chemical properties as in amphiphilic polymer. In the case of polyampholyte, previous theoretical studies have shown a complicated dependence of adsorption on the charge distribution along the chain and the flat surface composition. However, for amphiphilic polymers confined in a curved pore with non-Coulombic interaction between the stickers and the surface, according to our best knowledge, the theoretical study is still limited, resulting in a lack of understanding of the underlying mechanism of the relation between the sticker sequence and adsorption behavior of polymers.…”
Section: Introductionmentioning
confidence: 99%